Controllable synthesis of mesoporous titanosilicates for styrene oxidization using a nanocellulose template strategy. Issue 31 (31st March 2017) - Shen, Dazhi; Liu, Jian; Gan, Lihui; Huang, Naizhong; Long, Minnan
Abstract : A nanocellulose-template strategy is reported for the controllable synthesis of mesoporous titanosilicates as efficient catalysts for the oxidization of styrene. Abstract : In this work, mesoporous titanosilicates with tunable pore size were successfully synthesized using green and cheap bio-templates (nanocellulose). A series of samples was systematically prepared, characterized and used as catalysts for styrene oxidation by H2 O2 . The results demonstrated that the nanocellulose template strategy reported here was a feasible and effective method. The as-prepared titanosilicates presented high specific surface areas (450–500 m 2 g −1 ) and their mesopore sizes could be tuned from 2 to 8 nm by varying the addition amount of templates in the synthesis process. Active tetrahedral Ti species were efficiently incorporated in the mesoporous silica. Meanwhile, strong acid sites of the samples were confirmed using NH3 -TPD. The catalytic results revealed that the optimal catalysts (Si/Ti = 20 mol ratio) showed high catalytic activity and product selectivity can be adjusted through changing the mesopore size of the catalysts. The recycling tests indicated that as-prepared catalysts exhibited low catalytic deactivation. In addition, the oxidation mechanism over this catalyst was proposed. Thus, the present novel, sustainable and controllable method showed potential practical applications.